Enhancing Patient-Facing Ethics Resources at St. Joseph's Health System: A Mixed-Methods Approach - Cheetu, Shruti; Raza, Rubab; Srikanthan, Saranya; Zheng, Difei; Do, Phuong (Prepared by the McMaster Research Shop for St. Joseph's Health System, 2024)
The St. Joseph’s Health System (SJHS) Ethics Program is dedicated to supporting ethical decision-making in healthcare and is enhancing its resources to better serve diverse communities. The program wanted to understand the ethics education needs of patients, families, and healthcare providers by assessing its resources and the broader Ontario landscape to identify areas for improvement. SJHS recognizes that ethics resources are integral in guiding individuals through decision-making processes. However, without a structured assessment, it is unclear whether these resources are accessible, actionable, and inclusive for diverse populations. By evaluating existing materials and identifying gaps, this project helps ensure that SJHS ethics resources effectively support healthcare decisions.
Keywords: Hamilton, community-engaged research, healthcare ethics, ethics education, evaluation